The Writing on the Wall The Work of Joane Cardinal-Schubert - Sharman, Lindsey (Art in Profile: Canadian Art and Architecture, 2017)
Artist. Activist. Curator. Joane Cardinal-Schubert was a phenomenal talent. Her work recognizes the social and political ramifications of lived Indigenous experience, exposing truths about history, culture, and the contemporary world. She was a teacher and mentor, supporting those who struggle against the legacies of colonial history. She was an activist for Indigenous sovereignty, advocating for voices that go unheard. Despite significant personal and professional successes and monumental contributions to the Calgary artistic community, Cardinal-Shubert remains under-recognized by a broad audience. This richly illustrated, intensely personal book celebrates her story with intimacy and insight Combining personal recollection with art history, academic reading with anecdote and story, The Writing on the Wall is a crucial contribution to Indigenous and Canadian art history. Cardinal-Shubert's work leads the conversation, embracing the places where the personal, the political, and the artistic meet.